“Gestión del talento humano y su incidencia en la satisfacción de los empleados de la Mecánica automotriz Ferán Jr. Cantón Quevedo”. - Suarez Alcivar, Natalia Lizbeth (2025)
The objective of this study is to analyze the management of human talent and its impact on the job satisfaction of employees of the company Mecánica Automotriz Ferán Jr. located in the canton of Quevedo. The research was developed under a mixed approach, with qualitative and quantitative methods, of a transversal nature, allowing to obtain a comprehensive view of the causes of job satisfaction in relation to organizational management practices. For this purpose, interviews were conducted with the owner of the company and surveys were conducted with a population of employees, complemented with direct observation in the workplace. The results of the surveys revealed that, although most employees value interpersonal relationships and feel recognition from the company, there are deficiencies in internal communication and in the training and professional development processes. In addition, it was found that these practices have a significant influence on employee motivation and commitment, which are key aspects for performance and productivity. Statistical analysis showed a positive relationship between working conditions and employee satisfaction, highlighting the need to strengthen human talent management strategies. The findings show that, although the company implements some actions for the benefit of its employees, it is necessary to optimize training and communication programs to improve the work environment and promote the well-being of its personnel. In response, an improvement plan is proposed that includes strategies aimed at strengthening internal communication, enhancing training opportunities and recognizing performance, in order to increase job satisfaction, improve productivity and contribute to organizational development.